2011
DOI: 10.1007/s10620-011-1571-8
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Elevated Levels of Collagen Type IV and Hyaluronic Acid in Gastric Juice and Serum in Gastric Cancer and Precancerous Lesion

Abstract: The analysis of collagen type IV and HA in gastric juice and serum may provide a simple aid in diagnosing gastric cancer and evaluating whether metastasis is occurring or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…We think the higher MDA levels are related to previous gastric cancer status rather than biliary reactive gastritis after gastrectomy because MDA levels are not correlated with reactive gastritis demonstrated by previous study 12. Prostaglandin, hyaluronic acid, aromatic amino acids as well as RNA assay are also showed higher levels in gastric juice of patients with gastric cancer 16,17,29,30. CA 19-9 and CEA levels in gastric fluid have no diagnostic and prognostic value in patients with gastric cancer 27.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…We think the higher MDA levels are related to previous gastric cancer status rather than biliary reactive gastritis after gastrectomy because MDA levels are not correlated with reactive gastritis demonstrated by previous study 12. Prostaglandin, hyaluronic acid, aromatic amino acids as well as RNA assay are also showed higher levels in gastric juice of patients with gastric cancer 16,17,29,30. CA 19-9 and CEA levels in gastric fluid have no diagnostic and prognostic value in patients with gastric cancer 27.…”
mentioning
confidence: 78%
“…15,28 Prostaglandin, hyaluronic acid, aromatic amino acids as well as RNA assay are also showed higher levels in gastric juice of patients with gastric cancer. 16,17,29,30 However, the optimal methods are still lacking because no existing gastric cancer biomarker in gastric juice has been carefully validated on a large scale. In the present study, we focus on the peroxidation process of gastric mucosal injury and demonstrated positive correlation…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Down-regulated collagen IV expression was directly related to high histologic grade [18]. Patients with gastric cancer with lymph node metastasis had more collagen type IV than patients without metastases [29]. A positive link between COL4A3 expression and progression of gastric carcinoma indicated that COL4A3 could be used as a marker to measure the aggressiveness of gastric carcinomas.…”
Section: Discussionmentioning
confidence: 99%